Verbal Sexual Harassment Victim (Catcalling) Legal Protection in Human Rights Perspective in Indonesia - Indah Intania Daud; Moh. R. U. Puluhulawa; Mellisa Towadi (Estudiante Law Journal, 2022)
Sexual harassment provides a feeling of insecurity and comfort to the victim, even at a more severe level, the victim can experience trauma. The very broad scope of sexual harassment shows how complex the problem is. So widespread, verbal sexual harassment (indecent comments, sexually suggestive jokes and so on) or what is known as catcalling is an interesting issue to study. This is because verbal sexual harassment or catcalling often occurs in the community but is considered normal by the community, even though catcalling can create feelings of insecurity, comfort and even fear for the victim. The type of legal research in this research is normative legal research, which is a process to find a rule of law, legal principles, and legal doctrines in order to answer the legal issues faced. The approach used in this research is a statutory approach, namely research on legal products. In this study the authors found that legal protection for victims of catcalling is still inadequate, judging from the lack of accommodation of repressive legal protection, this is because there are no specific rules governing the act of catcalling.